Actual, social and ideal body image in Mexican adolescents and their relation with body dissatisfaction: gender differences (Imagen corporal actual, social e ideal y su relación con el descontento corporal en adolescentes mexicanos: diferencias por género - Cocca, Armando; Blanco Ornelas, José René; Peinado Pérez, Jesús Enrique; Viciana Ramírez, Jesús (Retos, 2016)
The purpose of the present study was to compare the perception of current (CBI), ideal (IBI), social body images (SBI), and body dissatisfaction (BD) by gender in Mexican primary and secondary school students. A total sample of 1,146 participants (550 girls and 596 boys) aged 11-16 participated in the study. All participants completed the Mexican computerized adaptation of the Contour Drawing Rating Scale. Results of one-way multivariate analysis of variance, followed by one-way univariate analyses of variance, showed that girls (ABI = 4.26; IBI = 3.53; SBI = 4.28; BD = 0.89) expressed a greater discrepancy between ideal and actual body shape, as well as lower scores of ideal body shape than boys (ABI = 4.28; IBI = 3.93; SBI = 4.31; BD = 0.61). However, no statistical differences were found between boys and girls in actual and social body shape. Although current and social body images are perceived in a similar way by adolescents in our sample regardless of gender, yet girls seem to be more responsive to social and environmental pressures related with body stereotype, this being reflected by a higher dissatisfaction and a thinner idealization of the body. Our findings suggest that we need to focus our attention on girls, especially in a phase of changes such as puberty, if we aim to design any intervention that could positively impact youth’s health through a proper body image. Resumen. El propósito de este estudio fue de comparar por género la percepción de la imagen corporal actual (CBI), ideal (IBI) y social (SBI), así como el descontento con el propio cuerpo (BD), en una muestra de estudiantes mexicanos de escuelas primarias y secundarias. Se seleccionó una muestra de 1.146 participantes (550 niñas y 596 niños) de entre 11 y 16 años de edad, que completaron la adaptación mexicana de la Contour Drawing Rating Scale. Los resultados de los análisis multivariados y univariados demuestran que las niñas (ABI = 4.26; IBI = 3.53; SBI = 4.28; BD = 0.89) sufren un mayor descontento corporal que los niños (ABI = 4.28; IBI = 3.93; SBI = 4.31; BD = 0.61), así como consideran que el cuerpo ideal sea mucho más delgado. No se encontraron diferencias significativas entre niños y niñas en la imagen corporal real y social. Aunque los adolescentes perciban de una manera similar su cuerpo independientemente del género, las niñas son más receptivas en lo que refiere a las presiones sociales del estereotipo corporal, reflejándose esto en un mayor descontento y en un ideal excesivamente magro de su cuerpo. Nuestros resultados sugieren la necesidad de enfocar la atención en las niñas, especialmente durante la pubertad, de cara a implementar intervenciones apropiadas que tengan un impacto real sobre la salud de los jóvenes a través de la construcción de una apropiada imagen corporal.